Implementation of Human Resources Scorecard-Based Human Resources Work System Design at PT. Suryasukses Abadi Prima - Aulia Nurwinda Septiani; Pompong B. Setiadi (Yayasan Ilomata, 2023)
PT. Surya Sukses Group is one of the largest plastic manufacturers in Indonesia. This company has been established since 1989 whose products have been used by many industries. This study aims to determine the stages of implementing the Human Resource Scorecard and measuring human resource performance based on the Human Resource Scorecard at PT. Surya Success Group. The Human Resource Scorecard is a way to measure and show the performance of a company's human resources in a comprehensive manner that is directly aligned with the company's vision, mission and goals. This study uses a four-perspective approach, namely the Financial Perspective; Customer Perspective; Internal Business Process Perspective; Learning and Growth Perspective. Data collection was obtained from research related to four perspectives from PT. Surya Success Group. So the total score of PT. Surya Sukses Abadi Prima in 2019 was 2,506 which was classified as a bad company performance and in 2020 it was 3,139 which was classified as a medium company performance.